A design on the collimator for boron neutron capture therapy (BNCT) research facility at the thermal column of TRIGA MARK II - S., Shalbi; Norazlianie, Sazali; W. N. W., Salleh (IOP Publishing, 2020)
The development of the Boron Neutron Capture Therapy (BNCT) facility in Malaysia can be performed at the thermal column of the Malaysia research reactor. TRIGA MARK II is one of the facilities that can provide neutron source for BNCT facility. The specification of neutron flux and the gamma dose rate must consider for the development of the BNCT facility as a safety precaution for this research. Based on previous research, the thermal column identified as a suitable place for BNCT facility. To design the neutron collimator for BNCT purpose, the characterization of material towards thermal neutron flux explored using TLD and Microspec-6 and the collimator design was simulate using Monte Carlo N-Particle (MCNP) software based on the characterize materials in order to produce high thermal neutron flux. The combination of lead, HDPE, 30% borated polyethylene and aluminium as collimator design D1 simulate the highest thermal neutron 1.5770 x 109 neutron.cm−2s−1 and suitable for BNCT research purpose at the thermal column.